An Investigation into the Effect of Using Geometric and Non-Geometric Shapes on the Desirability of Human Character Stylization in Children’s Narrative Fiction Illustration - Namin, Hajar Salimi (Journal of History Culture and Art Research, 2017)
This study aims to investigate the effect of teaching the using of geometric and non-geometric shapes on human character stylization created by undergraduate graphic design students with poor performance in illustration of children's narrative fiction. The research methodology includes an experimental research by pre- and post-testing with test group in the next stage. Statistical population of the study consists of female undergraduate sophomores of graphic design at Faculty of Arts, Al-Zahra University in 2017. The students were first subjected to pretesting, and then the training package was provided to them and they were again subjected to testing. 35 students are selected to conduct the research. The tools used in this study include files, materials in the books, articles and related sites, experiments and appraisal forms. The results show that there is a significant difference between the pre-test and post-test. The independent variable thus creates a significant difference in the test group and is able to improve the human character stylization implemented by undergraduate students of graphic design at the post-test stage. Therefore, it is suggested to employ using of geometric and non-geometric shapes in order to teach human character stylization to the students.